Penyuluhan Dunia Kampus Pertanian Kepada Siswa-Siswa Jurusan APHP (Agribisnis Hasil Pengolahan Pertanian) Di SMKN 1 Pakis Aji Jepara - Riany Aulia Shabila; Wahid Nur Fajri; Muhammad Amir Biky; Nurfahmi Fadlillah (Jurnal Kabar Masyarakat, 2024)
Department of Agricultural Processing Products is one of the departments at SMKN 1 Pakis Aji Jepara which prioritizes practice as well as theory. Students of the Department of Agricultural Processing Products are not only intended to work directly but are also encouraged to continue their higher education on campus. The lack of information on the campus world, especially in a field that is linear with the Department of Agribusiness of Agricultural Processing Products, namely agriculture, makes it less difficult for students to know the real campus world. Moreover, the teachers of SMKN 1 Pakis Aji Jepara have not been able to explain the campus world in detail due to the limited time focused on teaching the material. Therefore, a community service activity was carried out by Agricultural Campus Lecturers from Muria Kudus University, Muhammadiyah Purwokerto University and Muhammadiyah Tegal University in the form of counseling about the world of agricultural campuses to students of SMKN 1 Pakis Aji Jepara. The counseling techniques carried out are by presenting materials, introducing the campus world with videos and discussions. The activity was carried out with a presentation about the campus world, especially the agricultural campus with material on how to choose an agricultural campus, how to register on an agricultural campus, campus life, campus organizations, what to do when studying at an agricultural campus, agricultural campus majors that can be chosen according to the interests of the major, scholarships on the agricultural campus and so on. The counseling was carried out in the Multipurpose Room of SMKN 1 Pakis Aji Jepara with the number of counseling participants of 56 students majoring in Agricultural Processing Products of SMKN 1 Pakis Aji Jepara